Portability of learning objects using Web and digital TV technologies - Rodolpho, Everaldo Rodrigo [UNESP]; De Oliveira, Hilda Carvalho [UNESP] (My University, 2009)
The construction of educational digital content is an important process for distance education. The content is composed of learning objects - LOs for which standards have been defined in order to encourage the reuse and portability of LOs. In this sense, this paper proposes an implementation model of OA that facilitates portability and the possibility of collaborative construction. This model is implemented in a Web system, which allows export and import LOs to other systems, independent of management systems and content repositories. The viewing content can be made both in learning systems for the Web and for the Brazilian digital TV. This allows integration and alternative technologies of information and communication for distance education. The case study presented considers the standard SOs SCORM and can be extended to other standards.
Keywords: Digital TV; Distance education; E-learning; Learning objects; Metadata; SBTVD; SCORM